2015
DOI: 10.1093/nar/gkv1372
|View full text |Cite
|
Sign up to set email alerts
|

The histone chaperone sNASP binds a conserved peptide motif within the globular core of histone H3 through its TPR repeats

Abstract: Eukaryotic chromatin is a complex yet dynamic structure, which is regulated in part by the assembly and disassembly of nucleosomes. Key to this process is a group of proteins termed histone chaperones that guide the thermodynamic assembly of nucleosomes by interacting with soluble histones. Here we investigate the interaction between the histone chaperone sNASP and its histone H3 substrate. We find that sNASP binds with nanomolar affinity to a conserved heptapeptide motif in the globular domain of H3, close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(86 citation statements)
references
References 66 publications
(87 reference statements)
11
71
0
Order By: Relevance
“…A previous study demonstrated that sNASP can bind both monomeric H3 and an H3‐H4 dimer in complex with ASF1 in vitro (Bowman et al , ). Interaction with the monomeric H3 is mediated in part through NASP's TPR domain binding to the C‐terminus of H3 (Bowman et al , ). As importins interact with the N‐terminal region of histones, the C‐terminal region of H3 would be free to hand‐off to NASP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that sNASP can bind both monomeric H3 and an H3‐H4 dimer in complex with ASF1 in vitro (Bowman et al , ). Interaction with the monomeric H3 is mediated in part through NASP's TPR domain binding to the C‐terminus of H3 (Bowman et al , ). As importins interact with the N‐terminal region of histones, the C‐terminal region of H3 would be free to hand‐off to NASP.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind the experiment was as follows: as RbAp46 and HAT1 bind to H4 epitopes within the H3.1-H4 heterodimer (Murzina et al, 2008;Song et al, 2008) (Fig 4G), if tethered histones were folded with their endogenous counterpart, we would expect to see the recruitment of RbAp46 and HAT1 to both tethered H3.1 and tethered H4, whereas if histones were monomeric, we would expect to see recruitment to tethered H4, but not H3.1. Conversely, as sNASP interacts directly with H3 as a monomer and as an H3.1-H4 heterodimer (Bowman et al, 2016(Bowman et al, , 2017, we would expect to see recruitment to both tethered H3.1 and H4 if a heterodimer was present, but only to tethered H3.1 if the histones were monomeric. As ASF1 contacts both H3 and H4 through independent binding sites (English et al, 2005;Natsume et al, 2007), we may expect to see recruitment to both independent of the histone's oligomeric status.…”
Section: Histones Released From Their Tether Incorporate Rapidly At Amentioning
confidence: 95%
“…3Ab) has been characterized as a reader module for the H3 tail 25,26 , whereas the unrelated TPR domain of sNASP (Hif1 in yeast) 27 (FIG. 3B) also binds the H3 α3 helix 28 . HJURP 29 , Scm3 (REF.…”
Section: Mechanistic Insights Into Chaperoning Histonesmentioning
confidence: 99%
“…Curiously, sNASP, RBAP46 and ASF1 seem to be capable of engaging histones H3–H4 in a single co-chaperone complex 87,8991 . However, ASF1 and sNASP may have overlapping binding sites at the H3–H4 tetramerization interface 22,23,28 . Therefore, for sNASP and ASF1 to engage histones at the same time (the interaction between ASF1 and sNASP is histone dependent 87 ), additional H3–H4-binding sites may be present in sNASP to allow the partial handover of the H3–H4 tetramerization interface to ASF1.…”
Section: Mechanistic Insights Into Chaperoning Histonesmentioning
confidence: 99%
“…Fluorescence two-hybrid (F2H) assay F2H assays were performed as previously described (Bowman et al, 2016;Czarna et al, 2013). Briefly, assays were performed in borosilicate 8-well Lab-Teks (Thermo Scientific).…”
Section: Parp1 Inhibitor Treatment and H 2 O 2 Treatmentsmentioning
confidence: 99%